IMF Staff papers : Volume 9 No. 3. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 1962)
This paper discusses performance of Canadian markets for US dollars. US dollar deposits transferred by US residents from US banks to Canadian banks or other foreign banks are treated by the US Department of Commerce for balance of payments purposes as an item that contributes to the balance of payments deficit, that is, as a short-term capital outflow financed by an increase in US liquid liabilities to foreigners. In Canadian banks, deposits denominated in foreign currencies have for many years been increasing much more rapidly than those denominated in Canadian dollars. The foreign currency assets of the Canadian banks are the mirror image of their foreign currency deposits. In view of the balanced relationship of foreign currency assets and liabilities, and of current banking practices, it is virtually impossible to visualize sales by the chartered banks of dollar assets for other currencies without a parallel adjustment in their deposit liabilities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet